A multiproxy analysis of modern environmental change within a cypress swamp forest, Collier County, FL - Swick, Kathryn; Johanson, Erik N.; Comas, Xavier (DISCOVER ENVIRONMENT, 2024)
The Florida Everglades are a vast subtropical wetland that historically spanned over 1,000,000 hectares, but much of the Everglades has changed in the last 100 years due to anthropogenic activity. Collier County, situated in southwest FL and bordering the Gulf of Mexico, was subject to alteration in the form of logging, road building, and canal digging. These actions disrupted the natural sheet flow of water and had large environmental impacts on the region, impacts which are slowly being addressed by Everglades restoration efforts. The aim of this work was to observe environmental change at a cypress swamp forest in Collier County within the Big Cypress National Preserve. Using sediment core data including charcoal analysis, loss on ignition, and peat humification, as well as remote sensing techniques, this project uses a novel approach to assess local environmental conditions in the modern era for the region. While this analysis was based on a single core located at the study site, additional ground-penetrating radar profiles at the study site showed a consistent, laterally continuous distribution of subsurface interfaces, therefore suggesting that the core is representative of the conditions at this specific location. Historical records and contemporary data are used to evaluate environmental change over time, and satellite imagery is used to quantify vegetation health. Environmental change related to anthropogenic activity is noted, and evidence of progress from restoration efforts is observed from the last two decades in our study’s data.